Inovasi Rocket Stove sebagai Alat Pembakar Sampah Organik Minim Asap untuk Mendukung Pengelolaan Sampah Berkelanjutan di Desa Girimukti: Pengabdian - Annisa; Akbar Fadillah; Darel Saffana Darmawan; Efriliana Dian Aningrum; Fadhil Rahman Nurdin S; Fatin Khairunissa; Ilman Fahmi Mustapa; M. Brilyan Nurul Firdaus; Nadila Elsa; Nurul Saepul Rohman; Vivayani Wahyu Dewanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The problem that often occurs in the surrounding environment is generally the problem of waste. The lack of waste management facilities faced by the Girimukti village community and the continued existence of people's habit of burning rubbish openly causes thick smoke, unpleasant odors and environmental pollution. The method applied was Participatory Action Research (PAR), which actively involved the community from the stages of observation, socialization, construction, testing, to evaluation. The results indicate that the Rocket Stove effectively reduces the volume of organic waste, accelerates the combustion process, and produces lower smoke emissions compared to traditional open burning. Moreover, the ash produced can be reused as organic fertilizer, providing added value for local agriculture. This program not only introduces appropriate technology innovation but also encourages behavioral changes in waste disposal and management.